Study of Correlation and Diversity of Gastropods at Mangrove Ecosystem in Payum Beach, Merauke - Sendy Lely Merly; Reny Sianturi; Alfonsia Lusi Nini (Masyarakat Moluska Indonesia, 2022)
This study had two aims, first was to determine the index of diversity, evenness, richness and dominance of gastropods species in the mangrove ecosystem, to assess the important value index of mangroves in the mangrove ecosystem, and the second one to understand the association of gastropods and mangrove in the mangrove ecosystem in Payum Beach, Merauke Regency. This research was conducted in September-October2021. This research using method of transect with a 100 m lenght of transect size. The research location devided into two station that are distinguished by the mangrove ecosystem to see the associated mollusc species. There were 8 species of gastropods that were analyzed including: Terebralia palustris, Terebralia semistriata, Telescopium telescopium, Cassidula angulifera, Cerithidea obstusa, Littorina intermedia, Littorina pallencens, and Littorina scabra. The diversity index (H’) of gastropods is 1,9370 so it is categorized as moderate, meanwhile the richness index (R) is 0,86 and the dominance (C) 0,16 both of these categorized as low, whilst inversely proportional to the evenness index (E) which shows the number 0,93 which means high evenness so that the community is stable. Furthermore, there are 3 types of mangroves namely Bruguirea cylindrica, Lumnitzera racemosa, dan Aegialitis annulata. Nonetheless, the relationship between the abundance of individuals of gastropods and the presence of mangroves at the research sites at station I and station II tended to be weak.